2019
DOI: 10.1007/s12088-018-00776-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Inoculants Assisted Growth of Chrysopogon zizanioides Promotes Phytoremediation of Salt Affected Soil

Abstract: Restoration of salt-affected soil through cultivation Chrysopogon zizanioides is a promising approach. The two way benefit of such an approach is that reclamation of salt-affected soil concomitant to improve plant growth and increased yield of essential oil produced in the plants roots. Earlier studies showed physiological changes and reduced growth of C. zizanioides under salinity. In the present study, plant growth promoting microorganisms viz. Pseudomonas monteilii, Bacillus megaterium, Azotobacter chroococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…From Figure 2, all the MC concentrations were found to be more e ective than the control in both SB and BB at initial to nal days (0-d to 15-d) for plant height of okra. is result suggested that MC e ectively metabolized the soil nutrients, thereby mobilizing the nutrients to water-soluble forms that help to stimulate the crop height [36,40], but in the case of control, the lower amount of plant accessible due to lack of microbial inoculants. In the comparison between SB and BS base, the PH (as a case study) was considered as a growth parameter with okra and tomato crops (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…From Figure 2, all the MC concentrations were found to be more e ective than the control in both SB and BB at initial to nal days (0-d to 15-d) for plant height of okra. is result suggested that MC e ectively metabolized the soil nutrients, thereby mobilizing the nutrients to water-soluble forms that help to stimulate the crop height [36,40], but in the case of control, the lower amount of plant accessible due to lack of microbial inoculants. In the comparison between SB and BS base, the PH (as a case study) was considered as a growth parameter with okra and tomato crops (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to having EC values of less than 4 dSm −1 , sodic soils are found to have high pH values (>8.5) and ESP values (>15), which are effects of low exchangeable sodium in the soil, causing soil dispersion, reduced porosity, and poor water infiltration, resulting in low crop growth and yields. In salt‐affected soils, ESP and sodium adsorption ratio (SAR) indicators show that there is a high concentration of salts, a high electrical conductivity (EC), and a high pH value (Pankaj et al, 2019). Salinity occurs when the concentration of soluble salts in the soil increases, which in turn causes plants to succumb to water deficiency, eventually leading to the death of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Perennial aromatic grasses can thrive in different types of degraded soils (Gupta et al, 2021; Pandey et al, 2015). PGPR and arbuscular mycorrhizal fungi (AMF) were used as bio‐inoculants for the cultivation of perennial aromatic grasses such as V. zizanioides in salt‐affected soil (Pankaj, Singh, et al, 2019). In addition to decrease in soil salinity, authors reported a significant increase in growth and productivity of V. zizanioides with effect of PGPR and AMF.…”
Section: Introductionmentioning
confidence: 99%